Navigating regulatory landscape: A qualitative exploration of medical devices and in vitro diagnostic medical devices oversight in Zimbabwe through key stakeholder perspectives. - Charles Chiku; Talkmore Maruta; Fredrick Mbiba; Justen Manasa (PLoS ONE)
Medical devices and In Vitro Diagnostics (IVDs) are vital for public health and accessible healthcare. Still, there is an imbalance in high-quality products in Low and Middle-Income Countries (LMICs). Zimbabwe's regulatory framework for medical devices and IVDs is unclear, leading to ineffective compliance and surveillance. As a result, there are knowledge gaps regarding pre-market and post-market regulatory elements to ensure the safety, quality and performance of medical devices and IVDs used in Zimbabwe. Our study aimed to explore the current status of medical devices and IVD regulations in Zimbabwe. Semi-structured interviews were conducted with 12 regulators from the Medicines Control Authority of Zimbabwe (MCAZ) National Microbiology Reference Laboratory (NMRL), Medical Laboratory and Clinical Scientists Council (MLCScCZ) to understand the current status of medical devices and IVD regulations in Zimbabwe. Three participants completed a questionnaire to understand the regulatory landscape in Zimbabwe. Three key informant interviews were conducted with three regulators from the South African Health Products Regulatory Authority (SAHPRA), Tanzanian Medicines and Medical Devices Authority (TMDA), and World Health Organization Regulatory Systems Strengthening (WHO RSS) to learn best practices to create a roadmap for Zimbabwe. We analyzed qualitative data using a thematic analysis. The findings reveal significant deficiencies and gaps in the legal framework for regulating medical devices and IVDs, highlighting the need for a legal framework and the absence of more comprehensive regulations. Regulatory entities face capacity limitations, especially in regulating medical devices and IVDs. Conformity assessment processes, medical devices, IVD classification criteria, and post-market surveillance also represent challenges, highlighting the need for a well-defined framework and regulatory procedures. The Zimbabwean regulatory system pathway is reactive, prompting several regulatory initiatives to address needs. Despite facing challenges, there is recognition of the importance of collaboration among regulatory authorities, emphasizing a shared commitment to improving and strengthening medical devices and IVD regulations for improved patient safety. By advocating for a proactive, comprehensive, and legally sound approach, indicating the potential for collaboration and synergy, this study provides a foundation for well-informed policy recommendations to guide enhancements and build a framework for a resilient, efficient, and transparent regulatory environment in the Zimbabwe and African regions as a whole.